2007
DOI: 10.2176/nmc.47.299
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Cerebral Circulatory Disorders in Idiopathic Normal Pressure Hydrocephalus

Abstract: This study was conducted to elucidate the pathologic conditions of cerebral circulatory disorders in idiopathic normal pressure hydrocephalus (iNPH). Among 44 possible iNPH patients, 40 patients underwent shunt surgery based on diagnostic flow charts plotted by the Southern Tohoku method and were evaluated to be shunt-effective at the end of the first post-surgical month. The cerebral blood flow (CBF) was measured by N-isopropyl-( 123 I)-P-iodo-amphetamine single photon emission computed tomography (mean, mCBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
3
22
1
5
Order By: Relevance
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by single photon emission computed tomography utilizing radio-labeled materials including iodine-123 Nisopropyl-p-iodoamphetamine, 101,116,128) technetium99m hexamethylpropyleneamine oxime, 29,74,93) and technetium-99m ethyl cysteinate dimer, 47,67,143) positron emission tomography with 15 O-gas 97) and 15 O-H 2 O, 65,66) and nonradioactive xenon-CT. 130) In a study measuring CBF, hypoperfusion around the corpus callosum and sylvian fissures was observed and frontal dominant hypoperfusion has been reported in many studies, but posterior and diffuse hypoperfusion have also been reported. 67,74,116,129,143) When voxel-based analysis is performed, hypoperfusion around the sylvian fissures and the corpus callosum reflects dilation of the sylvian fissures and lateral ventricles, respectively.…”
Section: -B Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by single photon emission computed tomography utilizing radio-labeled materials including iodine-123 Nisopropyl-p-iodoamphetamine, 101,116,128) technetium99m hexamethylpropyleneamine oxime, 29,74,93) and technetium-99m ethyl cysteinate dimer, 47,67,143) positron emission tomography with 15 O-gas 97) and 15 O-H 2 O, 65,66) and nonradioactive xenon-CT. 130) In a study measuring CBF, hypoperfusion around the corpus callosum and sylvian fissures was observed and frontal dominant hypoperfusion has been reported in many studies, but posterior and diffuse hypoperfusion have also been reported. 67,74,116,129,143) When voxel-based analysis is performed, hypoperfusion around the sylvian fissures and the corpus callosum reflects dilation of the sylvian fissures and lateral ventricles, respectively.…”
Section: -B Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…116) There are many studies showing an association between improved symptoms and increased CBF after a shunt procedure 47,74,78,93,95,128,129) ; however, other studies report no association between the symptoms and CBF. 66) It was reported that regional CBF in iNPH patients with minimal triad symptoms was significantly lower than in healthy controls, but in all brain regions, there was no significant difference from those with apparent objective triad symptoms.…”
Section: -B Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…Both ventriculomegaly and a narrowed subarachnoid at the high convexity are observed in brain magnetic resonance (MR) images in about one percent of normal elderly subjects as well as in patients with iNPH [2]. Quantitative regional cerebral blood flow (rCBF) seemed to be reduced in iNPH patients [3], which raises the question whether quantitative rCBF is also reduced in patients with pre-clinical stage iNPH.…”
Section: Introductionmentioning
confidence: 99%
“…1) Cerebral circulatory disorders in patients with NPH can manifest as either of two pathophysiological conditions: circulatory disorder of the cerebral cortical region, and that of the thalamus-basal ganglia region, and various patterns may develop according to the disease stage. 15) Such discrepant explanations may derive from the absence of comprehensive understanding of NPH, which is actually a dynamic and divergent disease in Neurol Med Chir (Tokyo) 48, October, 2008 S. Tsutsumi et al…”
Section: Discussionmentioning
confidence: 99%